The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/pace.13831
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic predictors of pacemaker battery depletion: Diagnostic sensitivity, specificity, and clinical risk

Abstract: Background: Pacemaker battery depletion triggers alert for replacement notification and results in automatic reprogramming, which has been shown to be associated with relevant cardiorespiratory symptoms and adverse clinical events.Objective: Determine if electrocardiogram (ECG) pacing features may be predictive of pacemaker battery depletion and clinical risk.Methods: This is an ECG substudy of a cohort analysis of 298 subjects referred for pacemaker generator replacement from 2006 to 2017. Electronic medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Another limitation with the use of the ECG predictors is with patients without pacing or with synchronous AV pacing. However, the clinical impact of automatic reprogramming in this subset of patients was observed to be minimal . Parsonnet and Cheema reported that most patients do not outlive their pacemakers .…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Another limitation with the use of the ECG predictors is with patients without pacing or with synchronous AV pacing. However, the clinical impact of automatic reprogramming in this subset of patients was observed to be minimal . Parsonnet and Cheema reported that most patients do not outlive their pacemakers .…”
mentioning
confidence: 81%
“…When pacemaker batteries are depleted, different pacemaker manufacturers installed automatic reprogramming features to extend battery life before replacement. Reprogramming of the rate response, AV synchrony, and lower rate limit may occur depending on the device manufacturer . Adverse events have been reported to be associated with the need for battery replacement.…”
mentioning
confidence: 99%
See 3 more Smart Citations